In vitro suppression of the MMP-3 gene in normal and cytokine-treated human chondrosarcoma using small interfering RNA - Korakot Nganvongpanit (2018)
Background: Matrix metalloproteinase (MMPs) synthesized and secreted from connective tissue cells have been thought to participate in degradation of the extracellular matrix. Increased MMPs activities that degrade proteoglycans have been measured in osteoarthritis cartilage. This study aims to suppress the expression of the MMP-3 gene in in vitro human chondrosarcoma using siRNA.Methods: Cells were categorized into four groups: control (G.1); transfection solution treated (G.2); negative control siRNA treated (G.3); and MMP-3 siRNA treated (G.4). All four groups were further subdivided into two groups - treated and non-treated with IL-1β- following culture for 48 and 72 h. We observed the effects of gene suppression according to cell morphology, glycosaminoglycan (GAG) and hyaluronan (HA) production, and gene expression by using real-time polymerase chain reaction (PCR).Results: In IL-1β treated cells the apoptosis rate in G.4 was found to be lower than in all other groups, while viability and mitotic rate were higher than in all other groups (p < 0.05). The production of GAG and HA in G.4 was significantly higher than the control group (p < 0.05). MMP-3 gene expression was downregulated significantly (p < 0.05).Conclusion: MMP-3 specific siRNA can inhibit the expression of MMP-3 in chondrosarcoma. This suggests that MMP-3 siRNA has the potential to be a useful preventive and therapeutic agent for osteoarthritis. © 2009 Nganvongpanit et al; licensee BioMed Central Ltd.